Klasterisasi Petani Padi Sawah di Kota Metro Provinsi Lampung Menggunakan Algoritma K-Means Cluster dan Elbow Method - Trio Santoso; Fitria Saftarina (Journal of Agribusiness and Community Empowerment (JACE), 2020)
Metro City is one of the administrative cities in Lampung province, Indonesia and also one of important rice producing regions in Lampung. Application of intensive agriculture in trend of  declining area, low quality of land and differences of farmers internal characteristics that requires special treatment as solutions. Clustering farmers using the K-Means Cluster algorithm and Elbow Method can be used to facilitate policy makers determine programs and activities must be taken. Results showed that farmers are ideally grouped into 5 clusters (C1, C2, C3, C4 and C5). C1 members having  most family members (4,54 persons). C2 members are the oldest age (68 years old) with longest farming experience (52.00 years) but have lowest formal education (7.67 years), least family members (3.33 person) and lowest total area (0.37 hectare). C3 having highest formal education (14.60 years) and largest paddy fields (0.80 hectare) but don't use any pesticides in paddy cropping management. Whereas farmers in C4 have largest family members helped (2.00 people). Farmers in C5 are the youngest (45.50 years old) and having the shortest experience (29.50 years) but use the most types (4 brands) and amounts of pesticides (400.00 mm.hectare.rotation-1 ) in paddy field management practices in Metro City.